2020
DOI: 10.1136/jitc-2020-000667
|View full text |Cite|
|
Sign up to set email alerts
|

Short-course radiotherapy promotes pro-inflammatory macrophages via extracellular vesicles in human rectal cancer

Abstract: BackgroundTumor-associated macrophages (TAM) constitute the most abundant immune cells in the tumor stroma initiating pro-inflammatory (M1) or immunosuppressive (M2) responses depending on their polarization status. Advances in tumor immunotherapy call for a detailed understanding of potential immunogenic mechanisms of irradiation routinely applied in rectal cancer patients.MethodsTo test the effects of radiotherapy on TAM, we ex vivo irradiated tissue samples of human rectal cancer and assessed the phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
(54 reference statements)
2
28
1
Order By: Relevance
“… 92 Radiotherapy was shown to induce a re-programming of M2-like macrophages into M1-like macrophages. 93 , 94 The latter aspect could be specifically relevant in WT, as M2 macrophages are predominant. As neo-adjuvant radio- and chemotherapy are already included in the standard treatment for many pediatric solid cancers, it would be crucial to understand their putative immunomodulatory effects in this tumor entity and eventually consider them for a coherent combination therapy with checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“… 92 Radiotherapy was shown to induce a re-programming of M2-like macrophages into M1-like macrophages. 93 , 94 The latter aspect could be specifically relevant in WT, as M2 macrophages are predominant. As neo-adjuvant radio- and chemotherapy are already included in the standard treatment for many pediatric solid cancers, it would be crucial to understand their putative immunomodulatory effects in this tumor entity and eventually consider them for a coherent combination therapy with checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…SCPRT (2 × 5 Gy) was also found to be associated with a shift in the polarization of TAMs towards an M1-like pro-inflammatory phenotype in vitro and in vivo [ 165 ]. Similarly, in another study, irradiated macrophages (5 × 2 Gy) showed a reduced anti-inflammatory profile, increased phagocytosis and unaltered pro-invasive and pro-angiogenic capacities [ 166 ].…”
Section: The Effect Of Conventional Therapies On the Tumor Microenmentioning
confidence: 99%
“…Clinically, in patients with T3 rectal cancer, a short course of radiotherapy (neoadjuvant hyperfractionated 25 Gy in 10 fractions; surgery performed on day 2–5) promoted TAM repolarisation towards an M1-like proinflammatory phenotype. Interestingly, ex vivo modelling of this response suggested that HMGB1 in EVs from irradiated tumour cells could be responsible for this effect on TAM polarisation [ 38 ].…”
Section: Radiation Response In the Tumour Microenvironmentmentioning
confidence: 99%